Differential stability of mRNA species of Alcaligenes eutrophus soluble and particulate hydrogenases. - Oelmüller, U (1990)
The functional half-lives of Alcaligenes eutrophus hydrogenase mRNAs were determined by physiological studies. Evidence was obtained for a functional half-life of about 1 h for the soluble NAD-linked hydrogenase (HoxS) mRNA and 14 min for the particulate hydrogenase (HoxP) mRNA. The synthesis of active HoxS continued for about 4 h, albeit at a decreasing rate after inhibition of transcription, e.g., by rifampin. In this strain, the mRNA of HoxS appeared to be stable, while the mRNA of HoxP did not. Different species of hoxS mRNA were detected by the Northern (RNA) hybridization technique using as a probe plasmid pCH139 carrying hoxS structural genes. The sizes of the major hoxS mRNA species were 7.6, 6.2, 5.0, and 0.9 kb. The chemical half-lives of these species ranged from 1 h (5.0-kb mRNA) to 7 h (0.9-kb mRNA). Evidence for a specific cleavage of the 6.2-kb transcript yielding the 0.9-kb species was obtained from RNA-DNA hybridizations with subcloned hoxS DNA. The chemical half-life of total hoxP mRNA was 8 min.